PENGARUH MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KUALITAS KERJA GURU PADA SMK NEGERI 1 SEBERIDA KABUPATEN INDRAGIRI HULU - Triyono, Aris (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was in SMK Negeri 01 Seberida, Indragiri Hulu. This research purpose to know the influence of motivation and career development to teacher work quality at SMK Negeri 01 Seberida, Indragiri Hulu, partially and simultaneously. This research used interview and questioner by using multiple linear regression. The result of this research was obtained equation as follow  Y = -23.015 + 0.389X1 + 0.357X1 it means that motivation and career development is 0, so teacher work quality (Y) value is -23.015. Coefficient regression motivation variable (X1) is 0.389. It means that if motivation increase one unit, so the teacher work quality will increase to 0.389. The higher the motivation (X1) so the teacher work quality will get higher as well (Y). Coefficient regression variable career development (X2) is 0.357 it means that if independent variable increase by 1 unit, so the other independent variable’s value is constant and career development will increase by 1 unit so teacher work quality (Y) will increase by 0.357. F test simultaneous shows that Fcount is 3.192 with significance as 0.056. So, Fcount < Ftable (3.192<3.34) or Sig F > 5% (0.056>0.05). Because the F significancy value smaller than significance level 0.05 and Fcount < Ftable so Ho accepted and Hi rejected. It means that motivation and career development doesn’t influenced the teacher work quality simultaneously. It was obtained the R equal to 0.0431 closer to 0, so it shows that motivation and career development to teacher work quality having a weak and positive relation. By using the table analysis, R2 (R Square) or coefficient determination is 0.186. It means 18.6% teacher work quality variable was influenced by motivation and career development. And the 81,4%  was influenced by another variable that not include in this research